Metode Pembelajaran Kooperatif Tipe Student Teams Achievment Division (STAD) Dalam Menumbuhkan Antusiasme Belajar - Aswatun Hasanah; Faiq Ilham Rosyadi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2019)
The learning method is one of the important learning components and is interpreted as a way to realize learning objectives. This research is intended to describe the cooperative learning method type Student Teams Achievement Division (STAD). The focus of discussion in this study is to describe the enthusiasm of learning and describe the steps in applying Student Teams Achievement Division (STAD) as an effort to foster student enthusiasm for learning. This research is a library research by using a descriptive analysis method. The analysis technique in this study uses an interactive data analysis model developed by Miles & Huberman, namely: data collection, data reduction, data explanation and conclusions. The results of this study indicate that the Student Teams Achievement Division (STAD) type of cooperative learning methods in growing enthusiasm for learning can be applied in five stages as follows: first, preparing the learning material. Second, forming groups / teams. Third, determine the initial score. Fourth, building a solid group / team. And fifth, giving awards for the best team. Besides that, the Student Teams Achievement Division (STAD) type of cooperative learning method has many positive impacts for students including having the opportunity to express, express ideas, opinions and opinions, and be able to work together and foster social sensitivity with the surrounding environment. Keywords: Method, Cooperative Learning, Student Teams Achievement Division (STAD), Learning Enthusiasm.